2014
DOI: 10.21608/ejdr.2014.5812
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Agriculture on Productivity of Some Russian Parsley Varieties Under North Sinai Conditions

Abstract: Governorate to evaluate the productivity and quality of some Russian parsley varieties by using organic farming practices. Compost manure was added to the soil at three rates of 10, 15 and 20 m 3 /feddan. Seeds of different flat-leaf parsley varieties were sown (local, Leaf Breeze, Legendary Hero and Leaf Sandwich). The results showed that the increase in organic fertilization rates led to an increase in herb yield and its quality characters (chlorophyll pigment content in the leaves and essential oil yield). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Our results agreed, with the findings reported by Toaima et al; and (2018) on parsley, Azzaz et al;(2009) on fennel, (2012), Shirkhodaei et al; and Abdollahi et al;(2016) on coriander, Badran et al; on fennel, El-Sayed et al;(2017) on dill and El-Tarawy et al; on Caraway Essential oil analysis GLC analysis of parsley essential oil samples for the second season plants from the different treatments was illustrated in Table ( 6) and Figures (1&2). Twelve components were identified, most of them were hydrocarbons with low values compared to the oxygenated ones those had the high values.…”
Section: Vegetative Growthsupporting
confidence: 94%
See 4 more Smart Citations
“…Our results agreed, with the findings reported by Toaima et al; and (2018) on parsley, Azzaz et al;(2009) on fennel, (2012), Shirkhodaei et al; and Abdollahi et al;(2016) on coriander, Badran et al; on fennel, El-Sayed et al;(2017) on dill and El-Tarawy et al; on Caraway Essential oil analysis GLC analysis of parsley essential oil samples for the second season plants from the different treatments was illustrated in Table ( 6) and Figures (1&2). Twelve components were identified, most of them were hydrocarbons with low values compared to the oxygenated ones those had the high values.…”
Section: Vegetative Growthsupporting
confidence: 94%
“…In the same manner, on Syrian Cephalaria (Cephalaria syriaca) reported that total chlorophylls contents influenced by organic and biofertilization . Jahanshahi et al; on dill and Toaima et al; on parsley revealed the same observations.…”
Section: Vegetative Growthsupporting
confidence: 71%
See 3 more Smart Citations